A-145 Much Ado About Norming: Ethnic Differences Across Three Normative Systems for COWAT/FAS Performance. (17th August 2022) - Hawley, Nanako; Ikonomou, Vasilios C; Myers, Melissa A; Pizer, Jasmin H; Harrell, Murphy N; Hill, Benjamin D
Abstract: Objective: Demographic correction of cognitive data is being increasingly scrutinized. We compared phonemic fluency for African Americans and Caucasians using three normative systems. Methods: Controlled Oral Word Association Test (COWAT)/FAS raw scores for 321 African Americans (56.4% female, mean age 50 years, mean education 13 years) and a matched sample of 330 Caucasians (53.6% female, mean age 47, mean education 13.5 years) were converted to T-scores using three normative systems (Heaton et al., 2004; Mitrushina et al., 1999; Schretlen et al., 2010). ANOVA was used to compare differences for the overall sample as well as for education level (15 years) and age range (18-35, 36-50, 51-65, and >65 years old). Results: Normative outcomes were significantly different between African American and Caucasian participants [Heaton (F (1, 516) = 6.77, p=.01; Mitrushina F (1, 509) = 10.32, p=.001; Shretlen F (1, 516) = 14.15, p=.001]. Heaton norms were significantly different for ethnicity for all education levels except >15 years of education. Mitrushina meta-norms and CNNS (Schretlen et al., 2010) were significantly different for ethnicity on FAS scores only for >15 years of education. Heaton norms were significantly different for ethnicity for the ranges of 18-35 years old and 51-65 years old. Mitrushina meta-norms and CNNS were significantly different for ethnicity only for the 36-50 years range. None of the norming systems were significantly different for >65 years. Conclusions: The interpretation of FAS performance for African Americans and Caucasians differed by the normative system utilized with different effects for age and education noted between normative approaches.